The relationship between the individual and society in Italo Calvino’s novel "The Baron Who Lived in the Trees" - NOURA SAFAA ABDUL RASOUL, Asst. Lecturer; WASAN ABDUL HUSSEIN REDA, Asst. Lecturer (lark, 2026)
The novel "The Baron of the Trees" by Italo Calvino addresses the relationship between the individual and society from the perspective of the main character, Cosimo di Rondo, who decides to spend his life in the trees, rejecting the class life to which he belonged. "The Baron of the Trees" is part of Calvino’s larger narrative trilogy, "Our Ancestors," which includes three novels that embody different aspects of contemporary Europeans. This trilogy explores the origins of identity and human history, imagined in an unreal time and place. The trilogy is a model for discovering present-day identity by revisiting the past in the mirror of literature, and addresses complex issues of individual identity. Amid these events, between isolationist rebellion against society and the inevitability of communication in the struggle for identity, the novel demonstrates that this decision does not completely isolate the individual from society, and that a life of absolute rebellion can lead to a loss of social balance. Hence, the fundamental idea of ​​our study of Calvino’s novel becomes clear: the search for identity and personal freedom requires a full awareness of the individual’s relationship with the social circle surrounding him or her. The title "The Search for Identity in Western Literary Texts" constitutes a fundamental focus of this research. Identity in literature is an expression that encompasses awareness of the self and of life’s and social necessities. It is a vital aspect in literature that sheds light on the multidimensional nature of the human being.